Physical Properties of Biofoam from Cassava Starch: An Environmentally Friendly Alternative to Conventional Styrofoam - Zulaikha Al-Qordhiyah; Vera Pangni Fahriani; Fitri Yuliasari; Fayzah Ahmad; Angelita Sendi Sinaga (Universitas Muhammadiyah Purwokerto, 2026)
A study has been conducted on the manufacture of biofoam from cassava starch extract with the addition of peanut shell powder. There were 3 samples made in this study by heating using an oven (120°C, 140°C, 160°C) with the addition of magnesium stearate and ZnO. The quality characteristics of the synthesized biofoam were tested through water absorption tests, water content tests, leakage tests and biodegradable tests. The results of the water absorption test analysis obtained the percentage of each sample of 17.409%, 12.081%, and 4.049%. From these results, the temperature of 160°C which meets the SNI standard is 11.8682%. In the water content test, the percentage of each sample was 30.290%, 15.884%, and 9.615%. From these results, it has met the SNI standard of 26.12% except at a temperature of 120°C. In the leakage test, the results were obtained in the form of leaking samples on days 1, 2, and 4. In the biodegradable test, the percentage of each sample decomposed was 96%, 97%, and 100%, in the seventh week. Based on the biodegradable test, all samples can decompose well in a relatively fast time span and meet SNI, which is 100% for 60 days.